Stylet-driven leads compared with lumenless leads for left bundle branch area pacing: a systematic review and meta-analysis - Xuezhi Chen; Jianzeng Dong (BMC Cardiovascular Disorders, 2024)
Abstract Objective Left bundle branch area pacing (LBBAP) is a novel physiological pacing method for treating left ventricular dyssynchrony. LBBAP is often delivered using lumenless leads (LLL). However, recent studies have also reported the use of style-driven leads (SDL). This study is the first systematic review comparing the outcomes of LBBAP with SDL vs. LLL. Methods The review and meta-analysis included all available comparative studies published on Embase, PubMed, Web of Science, CENTRAL, and Scopus up to 6th March 2024. Results Eight observational studies were included in the review. Meta-analysis showed that success rates of LBBAP performed with LLL and SDL were comparable (OR: 1.72 95% CI: 0.94, 3.17 I2 = 38%). Duration of implantation and total procedural duration were significantly lower in LBBAP performed with SDL. The pacing threshold was significantly higher, while pacing impedance was significantly lower in the SDL compared to the LLL group. Pacing QRS interval, R-wave amplitude, and stimulus to peak left ventricular activation time were similar in the two groups. Intra-operative and post-operative dislodgement were significantly higher in the SDL group, but no difference was noted in intra-operative perforation and pneumothorax risk. Conclusion Limited evidence from observational studies with inherent selection bias shows that success rates for LBBAP may not differ between SDL and LLL. While implantation of SDL may be significantly faster, it carries a higher risk of lead dislodgement. Both SDL and LLL are associated with comparable pacing characteristics except for reduced pacing impedance with SDL.